Impact and Implementation of Simulation-Based Training for Safety - Federico F. Bilotta; Samantha M. Werner; Sergio D. Bergese; Giovanni Rosa (The Scientific World Journal)
Patient safety is an issue of imminent concern in the high-risk field of medicine, and systematic changes that alter the way medical professionals approach patient care are needed. Simulation-based training (SBT) is an exemplary solution for addressing the dynamic medical environment of today. Grounded in methodologies developed by the aviation industry, SBT exceeds traditional didactic and apprenticeship models in terms of speed of learning, amount of information retained, and capability for deliberate practice. SBT remains an option in many medical schools and continuing medical education curriculums (CMEs), though its use in training has been shown to improve clinical practice. Future simulation-based anesthesiology training research needs to develop methods for measuring both the degree to which training translates into increased practitioner competency and the effect of training on safety improvements for patients.